Gastrojejunal Anastomosis Perforation after Gastric Bypass on a Patient with Underlying Pancreatic Cancer: A Case Report and Review of the Literature - Omar Bellorin; Anna Kundel; Alexander Ramirez-Valderrama; Armando Castro (Case Reports in Surgery)
Introduction. We describe a case of gastrojejunal anastomosis perforation after gastric bypass on a patient with underlying pancreatic cancer. Case Description. A 54-year-old female with past surgical history of gastric bypass for morbid obesity and recent diagnosis of unresectable pancreatic cancer presents with abdominal pain, peritonitis, and sepsis. Computerized axial tomography scan shows large amount of intraperitoneal free air. The gastric remnant is markedly distended and a large pancreatic head mass is seen. Intraoperative findings were consistent with a perforated ulcer located at the gastrojejunal anastomosis and a distended gastric remnant caused by a pancreatic mass invading and obstructing the second portion of the duodenum. The gastrojejunal perforation was repaired using an omental patch. A gastrostomy for decompression of the remnant was also performed. The patient had a satisfactory postoperative period and was discharged on day 7. Discussion. Perforation of the gastrojejunal anastomosis after Roux-en-Y gastric bypass is an unusual complication. There is no correlation between the perforation and the presence of pancreatic cancer. They represent two different conditions that coexisted. The presence of a gastrojejunal perforation made the surgeon aware of the advanced stage of the pancreatic cancer.